Collaborative Innovation Model on 112 Call Center Service - Muhammad Irsyad Fadoli; Hardi Warsono (Universitas Medan Area, 2020)
This article aims to find out and explore how collaborative innovation is applied to the 112 call center service. The problem is focused on examining: First, what the condition of 112 call center service is . Second. how collaborative innovation is applied to e-government services. Third, the collaborative model of 112 call center service. To approach these problems, theoretical references from several experts on collaborative innovation and collaborative models were used. Data were collected through a library research as a writing framework and analyzed qualitatively. This study indicates that 112 call center service is a form of innovation in e-government applications. 112 call center service is an emergency service occurs in an area that must be handled as soon as possible. But this innovation do not always go well. It is since there are factors that hinder innovation. 112 call center service has not become a single call number and has not been integrated throughout Indonesia. Recommendation for overcoming it is by collaboration between institutions at both the central and regional levels. Collaboration is formed using the E-Government Integration (EGI) model, which is the relationship between the central institutions and the regional institutions, among agencies, and the relationship with service users, namely the community and the private sectors. This relationship is supported by variables of strategy, technology, policy and organization. It is expected that by applying the model 112 call center services can be integrated.